The Post 1990 Diplomacy Practices of Nepal - K.C., Khadga; Pandey, Niha (Tribhuvan University Journal, 2018)
In 21st century, the discourse of diplomacy has taken a new turn which has led to an emergence of advanced practices of Diplomacy. This alteration has influenced Nepal’s diplomatic practices wherein the practice of diplomacy transformed immensely. With this note, this paper primarily focuses on the diplomatic practices of Nepal post 1990. It reflects on the relationship between the regime and the diplomatic practices in reference to the systemic and the state level of analysis. It further emphasizes on the Public Diplomacy as a significant aspect while conducting diplomacy in the 21st century. Additionally, the analysis comprehends public diplomacy in relation with the democratic political structure. Next, Total Diplomacy is taken under scrutiny. The significance of Total Diplomacy in case of Nepal is discussed and the challenges of adapting Total diplomacy with the changing political structure are emphasized upon.